A Hydraulic Regenerative Braking System: Some Modeling and Experimental Results - Luyen, Van Hieu; Ngo, Sy Loc; Tran, Khanh Duong (Old Journal, 2018)
This paper presents a principle diagram of the proposed kinetic recovery system using the hydraulic accumulator. The proposed system installed on a 2.5 tone garbage specialized dump truck made in Việt Nam. The system is connected to the power take-off unit of the transmission system on the vehicle, could brake to recover kinetic energy of the vehicle. The dynamic equations of a braking process using hydraulic accumulator have been obtained and simulated using Matlab - Simulink program. The system has been tested, the experimental results are well in agreement. The influence of the accumulator initial pressure values on kinetic energy recovering process and efficiency of the system have been looked into and estimated. The system could be used to study characteristics of the hydraulic regenerative braking system extensively.